PENGARUH LINGKUNGAN SOSIAL TERHADAP IMAJINASI ANAK - Gunadi, Andi Ahmad (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2017)
The purposes of this study are: (1) to know the role of parents, teachers, peers, and society in the life of a child, 2) to know the development of imagination in children, 3) to know the social environment factor can influence the child's imagination. The formulation of the issue is whether the social environment affects the child's imagination? This research is descriptive quantitative research methods of correlation. X variable in this study is the social environment, the variable Y is Imagination. The population in this study is third grade students of State Elementary School. The result of the study is for homogeneity, comparing Fcount with Ftable the distribution Ftable, 0123<1.94 means homogeneous. To test for normality using K-S test, the social environment variables in mind that the value of quintile testers with α= 0.05 and n= 30 is 0.242, the highest value of 0.156. Ho accepted means Ha rejected due 0.156<0.242. The conclusion of the study is the normal distribution of the social environment at α= 0.05. The variable imagination of the students known that the quintile testers with α= 0.05 and n= 30 is 0.242, the highest value of 0.197. Ho accepted means Ha rejected due 0.197<0.242. The conclusion of the students imagination with normal distribution at α= 0.05. For a simple linear statistical test with product moment knowable Y=53.67+1.03X, of F=0.127 and Ftable =5.79, Fcount <Ftable is the linear regression. Finally, there is the influence of social environment on the imagination of the students.